3(u+9)=-4(3u-6)+6u

Simple and best practice solution for 3(u+9)=-4(3u-6)+6u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(u+9)=-4(3u-6)+6u equation:


Simplifying
3(u + 9) = -4(3u + -6) + 6u

Reorder the terms:
3(9 + u) = -4(3u + -6) + 6u
(9 * 3 + u * 3) = -4(3u + -6) + 6u
(27 + 3u) = -4(3u + -6) + 6u

Reorder the terms:
27 + 3u = -4(-6 + 3u) + 6u
27 + 3u = (-6 * -4 + 3u * -4) + 6u
27 + 3u = (24 + -12u) + 6u

Combine like terms: -12u + 6u = -6u
27 + 3u = 24 + -6u

Solving
27 + 3u = 24 + -6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '6u' to each side of the equation.
27 + 3u + 6u = 24 + -6u + 6u

Combine like terms: 3u + 6u = 9u
27 + 9u = 24 + -6u + 6u

Combine like terms: -6u + 6u = 0
27 + 9u = 24 + 0
27 + 9u = 24

Add '-27' to each side of the equation.
27 + -27 + 9u = 24 + -27

Combine like terms: 27 + -27 = 0
0 + 9u = 24 + -27
9u = 24 + -27

Combine like terms: 24 + -27 = -3
9u = -3

Divide each side by '9'.
u = -0.3333333333

Simplifying
u = -0.3333333333

See similar equations:

| x-146=70+10x | | 9x^3-15x^2+2=0 | | (cos(x)*cos(y)-cot(x))dx-(sen(x)*sen(y))dy=0 | | (cos(x)*cosy-cot(x))dx-(sen(x)*sen(y))dy=0 | | (5x)(2x+8y)= | | 3x^2+82x+418=0 | | 6x(30+6)=6 | | .11y+.09(y+8000)=2520 | | 11y+.09(y+8000)=2520 | | (5x)(10xy)= | | 0.5x+2=5x-43 | | 12h=9+84 | | b^2+6b-4=-2 | | 27x=9x-2 | | h(x)=4x^2+36 | | (cosx*cosy-cotx)dx-(senx*seny)dy=0 | | x^2-22x+437=0 | | -46+3x=80+12x | | (cosx*cosy-cotx)dx-(sinx*siny)dy=0 | | 11y=165 | | 3x^2+4x+14=0 | | 0.8+4.8=7.2 | | z-9.2=8.5 | | 6r-1+6r=119 | | 0=1.2z-3.6 | | 11z=99 | | -6.5=1.3y-1.3 | | -6=w+19 | | a+96-16=214 | | -34+1.7x=-11.9 | | 3+7m-1=6m+8-2m | | ((y^2)-(2xy)+(6x))dx-((x^2)-(2xy)+(2))dy=0 |

Equations solver categories